Tinjauan Fungsi Hisbah dalam Kegiatan Perekonomian - Ririn Noviyanti (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2017)
Supervision is a consequence of the emergence of activities related to group interests. In the classical Islamic era, hisbah is a supervisory board that serves to oversee the course of social activities in society on several aspects. No exception in the economic aspect. This research is a literature research using content analysis in reviewing the function of hisbah institution as supervisor in economic activity. The conclusion in this study states that hisbah has a function as an evaluator of economic activities that ensure economic activities run in accordance with Islamic Shari'a. Such as prohibiting the practice of usury and ihtikar in economic activities, guarding pricing, prohibit the sale and purchase of money, and so forth. Keywords: Hisbah, Supervision, Islamic Economics